Effect of distance from the support on the penetration mechanism of clamped circular polycarbonate armor plates - Hussain Shah, Qasim; Abakrb, Yousif A. (Elsevier, 2008)
A 1.91-mm thick circular polycarbonate plate of 115mm diameter was impacted by a spherical steel projectile of 6.98mm diameter at its center. Subsequent impacts were made at 10, 20, 30, 40, and 50mm radii of the plate. Dent dimensions for the damaged plate were measured using optical microscope. For a constant projectile velocity of 138ms1 which was below the perforation limit of the plate under investigation, a maximum thickness reduction close to the edge support was observed. The experimental work was modeled into explicit finite-element analysis program LSDYNA for simulations. LSDYNA was able to predict the dent depth and reduction in plate thickness at impact points precisely. In this research, the effect of the impact location distance from the supports on the damage mechanism of circular polycarbonate armor plates is investigated. The target plate was subjected to constant velocity projectile impacts starting at the plate midpoint and varying the impact distance from midpoint towards the clamped edge. Failure of plate is predicted close to the constrained boundary under uniform conditions.